واقع المسؤولية الاجتماعية للمؤسسات الصغيرة والمتوسطة في فترة انتشار جائحة كورونا - مزعاش, هيبة; ريغي, أسماء (جامعة الوادي University of Eloued, 2021)
هدفت هذه الدراسة إلى معرفة واقع المسؤولية الاجتماعية للمؤسسات الصغيرة والمتوسطة في ولاية برج بوعريريج خلال فترةانتشار جائحة كورونا، من خلال التطرق لمدى تبني المؤسسات الصغيرة والمتوسطة للأبعاد الخمسة للمسؤولية الاجتماعية أثناء انتشار الجائحة، عبر دراسة ميدانية تضمنت عينة من (60) مؤسسة صغيرة ومتوسطة تمت معالجة نتائجها باستخدام الأدوات والمؤشرات الإحصائية المتعارف عليها. توصلت هذه الدراسة إلى مجموعة من النتائج أهمها عدم وجود فروق في آراء اتجاهات أفراد العينة حول تطبيق المؤسسات الصغيرة والمتوسطة لأبعاد المسؤولية الاجتماعية، كما أن تطبيق أبعاد المسؤولية الاجتماعية في المؤسسات الصغيرة والمتوسطة يرتبط بعدة عوامل أهمهاحجم المؤسسة وتصنيفها، توفر الموارد الماليةوالظروف الاقتصادية المحيطة. This study aimed to know the reality of the social responsibility of small and medium enterprises in the state of Bordj Bou Arereridj during the Corona pandemic, by addressing the extent to which enterprises have adopted the five dimensions of social responsibility, through a field study that included of (60) enterprises that were addressed Its results using recognized statistical tools and indicators. This study reached of results is the absence of differences in the opinions regarding the application small and medium enterprises the dimensions of social responsibility, and the application of her dimensions is related to several factors are the size and classification of the institution, financial resources and economic conditions.
The reality of the social responsibility of small and medium enterprises in the period of the spread of the Corona pandemic -A case study of small and medium enterprises in the state of BordjBouArreridj
مقال
Keywords: المسؤولية الاجتماعية، المؤسسات الصغيرة والمتوسطة، جائحة كورونا،الأبعاد الخمسة، برج بوعريريج.